Analysis of Wave Characteristic in Fuel Terminal Serui - Mas'ud M, Ahmad Azwar; Suntoyo, Suntoyo; Pratikto, Widi A (Department of Marine Science, Faculty of Fisheries and Marine Universitas Riau, 2024)
The Serui Fuel Terminal is a vital state-owned facility distributing fuel oil throughout Yapen Island, Papua Province. However, this facility has a problem: waves or overtopping, which can even cause damage to existing facilities. This research aims to determine the hydrodynamic process and wave characteristics through theoretical analysis and numerical modeling using Mike21 with Hydrodynamic (HD) and Spectral Wave (SW) Modules. Bathymetry, current and tidal data collected in the field and wave data collected from ECMWF, calibration is carried out by comparing modeling output (currents & tides) with the results of observations and wave propagation and transformation study theoretically and compared with the results of wave modeling, so the accuracy of the modeling results can be reviewed. The validation results of tidal modeling with a MAPE (Mean Absolute Percentage Error) value of 0.3%, current modeling with a MAPE value of 30%, and waves from each orthogonal with an average MAPE of 15%. Generally, wave height on the shoreline is 0.3-0.4 m (calm waves), and the cause of the overtopping that occurs is due to the geometry and type of existing coastal buildings with smooth sloping sides and impermeable, which makes the wave height double with a run-up height 0.6-0.8 m.